Lithuanian Christian democracy. [Forews by Richard Giloth and Anthony J. Rudis. Introd. by V. Brizgys] (Pr.: "Draugas", 1976)
Bibl. Leo XIII Fund. Affiliate of the Lithuanian Christian Democratic Union.